Determining the Related Factors to the Survival Time of Inpatients With COVID-19 in Northern Iran: A Retrospective Study - Alireza Heidari; Mohammad Javad Kabir; Naser Behnampour; Zahra Khatirnamani; Amir Hossein Rahimi (Gonabad University of Medical Sciences, 2023)
Background: Coronavirus disease 2019 is a new viral disease and in a short period, it has affected the world in various economic, social, and health aspects. This disease had a high mortality rate at the time of its occurrence. This article aims to determine the related factors to the survival time of inpatients with COVID-19 in northern Iran. Methods: In this retrospective study, the data of 3480 patients with laboratory confirmation of the virus caused by COVID-19 infection in 17 hospitals covered by Golestan University of Medical Sciences from February 20 to July 20, 2020 were used. For all patients included in the study, until the end of the study, the follow-up has been done through the hospital information system unit. Statistical analysis was performed using R statistical software version 3.6.2 with a survival package.  Results: Out of 3480 definitive patients with COVID-19, the average age of the patients was 52.93±19.20 years and 51.1% of them were women. A total of 77.6% of patients recovered and 22.4% died at the end of the study (781 patients, 22.4%). The median survival time among deceased patients was less than one day (interquartile range [IQR]: 0-5) days. Patients with an age group above 49 years had a 2.1 times higher chance of death than other patients. Patients who had no history of hospitalization in the intensive care unit (ICU) had a 1.77 times higher chance of death than other patients. Patients who did not use ventilators had a 1.21 times higher chance of death than other patients. Conclusion: Finally, according to the results of this study, in the early days of hospitalization, it is necessary to investigate the spread of COVID-19 in people younger than 49 years, hospitalized in intensive care unit (ICU), and hospitalized in other cities.